Management of early pouch‐related septic complications in ulcerative colitis: a systematic review. (12th June 2018) - Worley, G. H. T.; Segal, J. P.; Warusavitarne, J.; Clark, S. K.; Faiz, O. D.
Abstract: Aim: It is well established that ileo‐anal pouch‐related septic complications (PRSC) increase the risk of pouch failure. There are a number of publications that describe the management of early PRSC in ulcerative colitis (UC) in small series. This article aims to systematically review and summarize the relevant current data on this subject and provide an algorithm for the management of early PRSC. Method: A systematic review was undertaken in accordance with PRISMA guidelines. Studies published between 2000 and 2017 describing the clinical management of PRSC in patients with UC within 30 days of primary ileo‐anal pouch surgery were included. A qualitative analysis was undertaken due to the heterogeneity and quality of studies included. Results: A total of 1157 abstracts and 266 full text articles were screened. Twelve studies were included for analysis involving a total of 207 patients. The studies described a range of techniques including image‐guided, endoscopic, surgical and endocavitational vacuum methods. Based on the evidence from these studies, an algorithm was created to guide the management of early PRSC. Conclusion: The results of this review suggest that although successful salvage of early PRSC is improving there is little information available relating to methods of salvage and outcomes. Novel techniques may offer an increased chance of salvage but comparative studies with longer follow‐up are required.